2021
DOI: 10.3390/molecules26040954
|View full text |Cite
|
Sign up to set email alerts
|

The Promising Ability of Humulus lupulus L. Iso-α-acids vs. Diabetes, Inflammation, and Metabolic Syndrome: A Systematic Review

Abstract: For centuries, natural medicines have represented the only option for treating human diseases and, nowadays, plant phytochemicals are considered as promising compounds to treat or prevent chronic conditions. Among them, hop flowers (Humulus lupulus L.), typically used in brewing industries to give the typical aroma and flavor to beer, have attracted particular attention for their health promoting properties. Several in vivo/vitro studies and human interventional trials have demonstrated the beneficial effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 74 publications
(132 reference statements)
3
13
0
Order By: Relevance
“…Humulones and the other bitter acids are susceptible to a natural isomerization process, by light exposure, use of boiling methods or hops extraction using an aqueous medium of increased pH (7.5–8.5), thus resulting in the formation of iso‐α‐acids [7,12] . In addition, these compounds have been increasingly reported in the literature as some of the main anti‐inflammatory agents in hops, [6,33,36–38] which also corroborate our findings. Nozawa et al.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…Humulones and the other bitter acids are susceptible to a natural isomerization process, by light exposure, use of boiling methods or hops extraction using an aqueous medium of increased pH (7.5–8.5), thus resulting in the formation of iso‐α‐acids [7,12] . In addition, these compounds have been increasingly reported in the literature as some of the main anti‐inflammatory agents in hops, [6,33,36–38] which also corroborate our findings. Nozawa et al.…”
Section: Resultssupporting
confidence: 89%
“…The prenylated phloroglucinol homologs, humulone, cohumulone and adhumulone and its respective isomerized homologs are the main α‐acids found in different hop cultivars according to literature data [32] . Studies have shown that these compounds display potent anti‐inflammatory activity, through PGE2 inhibition by in vitro and in vivo models, [6,33] which corroborate our findings. The humulone was reported in the literature as a potent inhibitor on the 12‐ O ‐tetradecanoylphorbol‐13‐acetate (TPA)‐induced ear oedema anti‐inflammatory model when compared to the steroidal anti‐inflammatory drug hydrocortisone and the nonsteroidal indomethacin [34] .…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Recently, treatment with iso-α-acid extracted from hops was found to soothe or prevent different ailments such as liver steatosis, inflammation, and fibrosis as well as metabolic disorders such as obesity and diabetes ( [43,44], and reference therein).…”
Section: As Medicinal Cropmentioning
confidence: 99%
“…Furthermore, recent reports have highlighted the antiproliferative, anticancer [9,10], antiinflammatory [11,12] and antimicrobial [13] properties of hops due to the presence of phenolic compounds including terpenes, humulones (α-acids), lupulones (β-acids) and prenylated flavonoids secreted by lupulin glands [13]. For example, treatments with isoα-acids extracted from hops proved to be efficient in relieving the symptoms of various diseases such as liver steatosis and fibrosis, as well as obesity and diabetes [14,15].…”
Section: Introductionmentioning
confidence: 99%